Dual-heterogeneous particle reinforced aluminum matrix composite and method of making same
Patent Information
- Application Number
- CN202510103022.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-01-22
AI Technical Summary
当对颗粒增强体铝基复合材料施加载荷时,力会从较软的铝基体经过铝基体-颗粒增强体界面传递至硬的颗粒增强体,使得材料强度提升,但颗粒增强体同样会导致材料的塑性和延展性大幅降低
[0024] (1) The method for preparing the dual heterogeneous particle-reinforced aluminum matrix composite material proposed in this invention yields a composite material with excellent mechanical properties characterized by synergistic improvement in strength and plasticity. Results from the embodiments of this invention show that the yield strength of the dual heterogeneous particle-reinforced aluminum matrix composite material provided by this invention reaches 379.4 MPa, the ultimate tensile strength reaches 405.7 MPa, and the elongation reaches 12.7%. Its comprehensive mechanical properties are significantly improved compared to existing technologies.
Smart Images

Figure CN119898086B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material technology, and specifically relates to a dual heterogeneous particle reinforced aluminum matrix composite material and its preparation method. Background Technology
[0002] Particle-reinforced aluminum matrix composites are widely used in most aerospace structural components due to their excellent comprehensive properties, including high specific strength, light weight, high specific modulus, good thermal conductivity, and corrosion resistance. When a load is applied to a particle-reinforced aluminum matrix composite, the force is transferred from the softer aluminum matrix through the aluminum matrix-particle reinforcement interface to the harder particle reinforcement, thus increasing the material's strength. However, the particle reinforcement also leads to a significant reduction in the material's plasticity and ductility.
[0003] Heterogeneous structure design is a crucial method for achieving synergistic enhancement of strength and plasticity in metallic materials, and it is increasingly favored by researchers in metallic structural materials. Simultaneously introducing soft and hard domains with significant differences in hardness into a material facilitates dislocation stacking and interaction during deformation, resulting in higher heterogeneous deformation-induced strengthening and achieving excellent strength-plasticity matching. Currently, introducing heterogeneous structures into particle-reinforced materials has become an important solution to the strength-plasticity contradiction, such as layered structures, core-shell structures, and dual heterogeneous structures. Among these, dual heterogeneous structures are considered a very promising strategy, where the matrix grains exhibit a bimodal distribution, and the reinforcing particles exhibit a heterogeneous distribution. This forms soft and hard domains with significant differences in hardness, and a strain gradient is generated at the domain interfaces, forming geometrically necessary dislocations (GNDs), making the hard domain softer and the soft domain harder. Theoretical analysis suggests that the strong plasticity is due to the constraint of the domain interface. In the soft domain, dislocation pile-up forms near the domain interface. As the dislocation pile-up intensifies, these dislocations form a force that acts on the dislocation source and inhibits its emission of dislocations. At this point, the dislocation source needs to increase the external stress to excite dislocations. The external stress is the heterogeneous deformation induced stress, which avoids premature necking and thus improves plasticity.
[0004] Currently, spark plasma sintering (SPSS) has become a mainstream powder metallurgy technique for preparing particle-reinforced aluminum matrix composites. It utilizes a powerful DC pulsed current to induce localized discharges between metal powder particles, generating Joule heating to heat the sample. This process can also break down the oxide film on the surface of the metal powder, promoting the formation of sintering necks and resulting in rapid densification of the prepared particle-reinforced aluminum matrix composite. Furthermore, due to the short sintering time and low sintering temperature, it avoids the formation of hard and brittle phases that degrade performance, and prevents excessive grain growth. Therefore, a novel method for preparing dual heterogeneous particle-reinforced aluminum matrix composites can be developed based on SPSS technology. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a dual heterogeneous particle reinforced aluminum matrix composite material and its preparation method. The dual heterogeneous particle reinforced aluminum matrix composite material provided by this invention has the advantage of synergistic improvement in strength and plasticity.
[0006] To achieve the above objectives, the present invention discloses the following technical solution:
[0007] On one hand, the present invention provides a dual heterogeneous particle-reinforced aluminum matrix composite material, which includes nine layers of alternating stacked and cold-rolled hard and soft domains, wherein the hard domain is a composite material composed of fine-grained 6061 aluminum alloy and TiC nanoparticle reinforcement, and the soft domain is a coarse-grained 6061 aluminum alloy homogeneous material.
[0008] Preferably, the volume ratio of 6061 aluminum alloy to TiC nanoparticle reinforcement in the hard domain is 99.5:0.5.
[0009] On the other hand, the present invention provides a method for preparing a dual heterogeneous particle-reinforced aluminum matrix composite material, which includes the following steps:
[0010] S1. Using a soft domain as the first layer, nine layers of hard and soft domain material powders are alternately stacked and compacted, and then a nine-layer composite material is prepared by spark plasma sintering.
[0011] S2. The composite material is subjected to multiple cold rolling passes with a reduction of 90%, and then annealed at 400°C for 10 minutes at a reduction of 50%.
[0012] S3. After multiple cold rolling passes, the rolled composite material is subjected to heat treatment, which includes solution heat treatment and aging heat treatment. The holding temperature of the solution heat treatment is 550-570℃ and the holding time of the solution heat treatment is 5-60 min. The holding temperature of the aging heat treatment is 150-200℃ and the holding time of the aging heat treatment is 1-5 h. After the heat treatment is completed, a dual heterogeneous particle reinforced aluminum matrix composite material is obtained.
[0013] Preferably, in step S3, the solution heat treatment is performed at a holding temperature of 570°C for 30 minutes.
[0014] In step S3, the aging heat treatment is performed at a holding temperature of 175°C for 3 hours.
[0015] Preferably, the cold-rolled composite material includes three deformation stages. The first deformation stage is an elastic deformation process, similar to that of homogeneous materials. The second deformation stage is an elastoplastic transition process, where stress activates dislocation sources in the soft domains, causing plastic deformation, while the hard domains maintain elastic strain, resulting in mechanical incompatibility. The hard domains constrain the soft domains, limiting and increasing their strain, and a strain gradient is generated at the domain interfaces. Through the coordination of geometrically necessary dislocations, the properties of the soft and hard domains are changed, improving the overall yield strength. Dislocation pile-up occurs at the soft domain interfaces, and additional stress is required from the dislocation sources to excite dislocations. Through the pile-up of geometrically necessary dislocations, heterogeneous deformation-induced stress is generated, strengthening the soft domains. The third deformation stage is a surface strain distribution process, where continuous strain causes the hard domains to begin plastic deformation. Strain distribution increases the strain in the soft domains, and the strain gradient at the boundary between the soft and hard domains increases. Through the accumulation of more geometrically necessary dislocations, strain hardening capability is provided, preventing necking, and enabling the composite material to simultaneously possess high strength and high plasticity.
[0016] Preferably, step S1 specifically includes the following sub-steps:
[0017] S11. Preparation of hard domain powder: 99.5 vol.% of 6061 aluminum alloy powder and 0.5 vol.% TiC nanoparticle reinforcement were placed in a planetary ball mill for ball milling and mixing. The planetary ball mill contained three types of steel balls with diameters of 8 mm, 6 mm and 2 mm, respectively, in a mass ratio of 2:3:5 and a ball-to-material ratio of 8:1, to obtain hard domain powder after ball milling.
[0018] S12. Coarse-grained 6061 aluminum alloy powder and ball-milled hardened powder are alternately stacked into 9 layers, compacted, and then placed in a spark plasma sintering system to apply temperature and pressure to prepare a sintered 9-layer composite material.
[0019] Preferably, the obtained dual heterogeneous particle reinforced aluminum matrix composite has a yield strength of 379.4 MPa, an ultimate tensile strength of 405.7 MPa, and an elongation of 12.7%.
[0020] Preferably, the fine-grained 6061 aluminum alloy powder has a particle size of <10 micrometers, the TiC nanoparticle reinforcement has a particle size of 50 nanometers, and the coarse-grained 6061 aluminum alloy powder has a particle size of greater than 45 micrometers and less than 150 micrometers.
[0021] Preferably, in step S11, argon is used as the protective atmosphere during the powder loading process; the total working time of the planetary ball mill is 2-2.5 hours, and it stops for 10 minutes after working for 15 minutes, with a rotation speed of 150-250 rpm.
[0022] Preferably, in step S12, the sintering heating and pressurization process is as follows: 0 min - 2 min, temperature rises to 20°C; 2 min - 6 min, temperature rises to 100°C; 6 min - 12 min, temperature rises to 200°C; 12 min - 20 min, temperature rises to 300°C; 20 min - 32 min, temperature rises to 400°C; 32 min - 48 min, temperature rises to 530°C; 48 min - 50 min, temperature rises to 540°C; 50 min - 52 min, temperature rises to 550°C; 52 min - 54 min, temperature rises to 560°C; 54 min - 57 min, temperature is maintained at 560°C; 2 min - 57 min, pressure is maintained at 50 MPa.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The method for preparing the dual heterogeneous particle-reinforced aluminum matrix composite material proposed in this invention yields a composite material with excellent mechanical properties characterized by synergistic improvement in strength and plasticity. Results from the embodiments of this invention show that the yield strength of the dual heterogeneous particle-reinforced aluminum matrix composite material provided by this invention reaches 379.4 MPa, the ultimate tensile strength reaches 405.7 MPa, and the elongation reaches 12.7%. Its comprehensive mechanical properties are significantly improved compared to existing technologies.
[0025] (2) The composite material proposed in this invention is formed by alternating stacking of hard domains formed by fine-grained 6061 aluminum alloy and TiC nanoparticle composite material and soft domains formed by coarse-grained 6061 aluminum alloy homogeneous material. Multi-pass cold rolling is employed, with a final reduction of 90%. Compared to the ordinary control group, the cold-rolled dual heterogeneous particle reinforced aluminum matrix composite material exhibits excellent strength-plasticity matching. This is attributed to the mechanical incompatibility under strain caused by the difference in strength and hardness between the soft and hard domains, leading to dislocation pile-up. Dislocation sources require heterogeneous deformation-induced stress to be activated, resulting in increased strength. Ultimately, the hard domains become "softer," and the soft domains become "harder," while the accumulated geometrically necessary dislocations provide HDI hardening capability, improving plasticity. Subsequently, heat treatment under different conditions is performed. After solution treatment at 570℃ for 30 minutes, the precipitated phases completely dissolve, and the dual heterogeneous particle reinforced aluminum matrix composite material undergoes complete recrystallization, resulting in optimal comprehensive mechanical properties.
[0026] (3) In the preparation method of the dual heterogeneous particle reinforced aluminum matrix composite material proposed in this invention, the optimal solution-aging treatment conditions were obtained by combining different heat treatment conditions with mechanical analysis. The solution-treated dual heterogeneous particle reinforced aluminum matrix composite material was aged at 150-200℃ for 1-5h. Different aging treatment temperatures all showed peak aging performance. 175℃ was selected as the optimal aging temperature, and 3h was selected as the optimal aging time. At this time, a large number of β” phases were distributed in the matrix, which is in the peak aging state, which can ensure the high strength of the material. The resulting composite material has excellent mechanical properties with synergistic improvement in strength and plasticity. Attached Figure Description
[0027] Figure 1 This is a schematic diagram of the overall process of the present invention;
[0028] Figure 2 The OM diagram of the sintered dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 1 of this invention;
[0029] Figure 3 The OM diagram of the cold-rolled dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 2 of this invention;
[0030] Figure 4 The image shows the OM diagram of the dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 3 of this invention after solution heat treatment at 570℃ for 5 min.
[0031] Figure 5 The OM diagram of the dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 4 of this invention after solution heat treatment at 570℃ for 30 min is shown.
[0032] Figure 6 The image shows the OM diagram of the dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 5 of this invention after solution heat treatment at 570℃ for 60 min.
[0033] Figure 7 This is a TEM image of the aluminum matrix composite material with dual heterogeneous particles after aging heat treatment at 175℃ for 1 hour prepared in Example 6 of the present invention.
[0034] Figure 8 This is a TEM image of the aluminum matrix composite material reinforced with two heterogeneous particles after aging heat treatment at 175℃ for 3 hours prepared in Example 7 of the present invention.
[0035] Figure 9 This is a TEM image of the aluminum matrix composite material reinforced with two heterogeneous particles after aging heat treatment at 175℃ for 5 hours prepared in Example 8 of the present invention. Detailed Implementation
[0036] Exemplary embodiments, features, and aspects of the present invention will now be described in detail with reference to the accompanying drawings. The same reference numerals in the drawings denote elements that have the same or similar functions. Although various aspects of the embodiments are shown in the drawings, they are not necessarily drawn to scale unless specifically indicated otherwise.
[0037] On one hand, the present invention provides a dual heterogeneous particle-reinforced aluminum matrix composite material, comprising nine alternating layers of hard and soft domains. The hard domains are a composite material composed of fine-grained 6061 aluminum alloy and TiC nanoparticle reinforcement, while the soft domains are a coarse-grained homogeneous 6061 aluminum alloy. The volume ratio of 6061 aluminum alloy to TiC nanoparticle reinforcement in the hard domains is 99.5:0.5.
[0038] The dual heterogeneous particle-reinforced aluminum matrix composite material of this invention, based on the fine-grained reinforcement provided by the nanocrystals in the hard domain, forms multiple reinforcement mechanisms, such as Orowan reinforcement, load-bearing reinforcement, and Taylor reinforcement, by introducing TiC nanoparticle reinforcement into the hard domain. This further increases the hardness difference between the soft and hard domains, reaching 64.09%. The deformation process is divided into three stages. In the first stage, both the soft and hard domains participate in elastic deformation, a process similar to that of homogeneous materials. In the second stage, stress first activates dislocation sources within the soft domain, causing them to emit dislocations and undergo plastic deformation on the slip surface. At this time, the hard domain is still in an elastic strain state, and mechanical incompatibility occurs at the interface between the two. Due to the rigid constraint of the hard domain on the soft domain, the soft domain cannot deform freely. Since the soft domain deforms first, it will bear more strain during the deformation process, and the strain is continuous at the domain interface. Therefore, a strain gradient is generated near the domain interface, requiring geometrically necessary dislocations to coordinate. This makes the soft domain "harder" and the hard domain "softer," improving the overall yield strength of the material. Due to the constraints of the domain boundaries, dislocation pile-ups form near the domain boundaries in the soft domain. As the pile-ups intensify, these dislocations create a force that acts on the dislocation source and inhibits its emission. At this point, the dislocation source requires additional external stress to continue exciting dislocations. The additional stress caused by the pile-ups of geometrically necessary dislocations is called back stress, which acts on the soft domain. Simultaneously, this force generated by the pile-ups of geometrically necessary dislocations also acts on the hard domain, called pre-stress. The combination of back stress and pre-stress is collectively referred to as heterogeneous deformation-induced stress. Ultimately, this will make the coarse grains stronger, with yield strengths even far exceeding those predicted by the mixing rule. In the third deformation stage, as strain continues to be applied, the fine grains, i.e., the hard domains, also participate in plastic deformation. Due to the existence of strain distribution, the soft domains experience higher strains than the hard domains. When adjacent domains experience different plastic strains, strain gradients exist near the boundaries of the soft and hard domains. These strain gradients increase with the increase of strain distribution, requiring more geometrically necessary dislocations to reconcile them. These accumulated geometrically necessary dislocations provide additional strain hardening capacity, helping to prevent necking during tensile testing and thus improving plasticity. Therefore, the composite material provided by this invention possesses excellent properties of high strength and high plasticity.
[0039] In the tensile fracture morphology, larger cracks in the hard domain were observed to stop propagating and become passivated at the interface with the soft domain. This indicates that the soft domain effectively prevented further crack propagation, a phenomenon also observed in other heterostructures. The underlying mechanism is that the soft domain provides more space for dislocation movement, facilitating dislocation migration and thus contributing to crack passivation.
[0040] The increased hard domain strength is mainly attributed to grain refinement and the presence of TiC particles. The addition of TiC nanoparticle reinforcement significantly improves the material's strength. When particle-reinforced aluminum matrix composites are subjected to stress, multiple strengthening mechanisms work together. TiC nanoparticles with a diameter of less than 1 μm promote the Orovan strengthening mechanism, which can be expressed by the following formula:
[0041]
[0042] Among them, G M V is the shear modulus of the aluminum matrix, b is the Burgers vector of the aluminum matrix, and V is the shear modulus of the aluminum matrix. p It is the volume fraction of the enhanced particles, d p Φ is the size of the reinforcing particles, and Φ is a proportionality constant.
[0043] When an external force is applied to DPARMCs, dislocations cannot pass through the TiC nanoparticle reinforcement. Instead, the TiC nanoparticles pin the dislocations, causing them to bend and form Orovan dislocation loops. When there is a significant hardness difference between the aluminum alloy matrix and the TiC nanoparticles, stress is transferred from the aluminum alloy matrix to the TiC nanoparticles through the aluminum alloy matrix-TiC interface. These nanoparticles then bear a larger proportion of the stress, thereby increasing strength. This load-bearing strengthening effect is expressed by the following formula:
[0044] Δσ=0.5V p σ Al
[0045] Where, σ Al It is the yield strength of the aluminum alloy matrix, V p It refers to the volume fraction of the enhanced particles.
[0046] During the preparation of DPMRAMCs, including sintering and subsequent solution treatment, dislocations form at the interface between the reinforcement and the matrix upon cooling to room temperature due to the significant difference in the coefficients of thermal expansion between the aluminum alloy matrix and the TiC nanoparticles. This leads to Taylor strengthening, as shown in the following formula:
[0047] Δσ=βGbρ 1 / 2
[0048] Where β is a constant, G is the shear modulus of the aluminum matrix, b is the Burgers vector of the aluminum matrix, and ρ is the dislocation density.
[0049] Therefore, Orovan strengthening, load-bearing strengthening, Taylor strengthening, and grain refinement strengthening lead to a significant strength difference between the hard and soft regions, resulting in the HDI effect and achieving a synergistic enhancement of the strength and ductility of cold-rolled DPMACs. After solution heat treatment, the increase in elongation (EL) and the decrease in yield strength / tensile strength (YS / UTS) are mainly attributed to recovery and recrystallization. However, when the solution time was increased from 5 minutes to 30 minutes, both YS and UTS were observed to increase, due to the dissolution of the Mg2Si and AlFe(MnCr)Si phases. The high diffusion rate of Mg and Si atoms in the aluminum alloy matrix leads to the rapid dissolution of solute atoms. Therefore, with increasing solution time, the solute atom concentration increases, exacerbating lattice distortion and increasing the resistance to dislocation movement. When the solution treatment time is extended to 60 minutes, the strength decreases. This is due to significant grain growth, which can be described by the Hall-Page relation, as shown in the following formula:
[0050] σ y =σ 0y +k y ·μ d -1 / 2
[0051] Where, σ 0y It is the internal friction force of dislocation movement within the grain, k y It is the Hall-Page slope, σ y It is the yield strength at room temperature, μ d It is the average grain size.
[0052] Coarse grains lead to reduced grain boundary density, and grain boundaries are key factors hindering dislocation movement, thus reducing strength. Extending solution treatment time results in aberrant grain growth in hard domains, reducing strength while increasing ductility. A common phenomenon after heat treatment of aluminum alloys is high strength accompanied by low ductility. This behavior is partly due to reduced strain hardening capacity, impairing the material's ability to accumulate and store dislocations within the grains, making it more susceptible to localized plastic instability. On the other hand, grain boundaries in the second-phase soft domains act as strong pinning sites, restricting dislocation movement. This reduces the number of dislocations crossing the soft domain boundaries, lowers the number of GNDs, weakens HDI hardening, and ultimately fails to improve ductility. In this invention, a synergistic enhancement of strength and ductility is observed, attributed to hardening of the soft domains through HDI stress, thereby increasing strength. The geometric strain gradient between the soft and hard domains further promotes HDI hardening, preventing necking in tensile tests and improving ductility.
[0053] On the other hand, the present invention provides a method for preparing a dual heterogeneous particle-reinforced aluminum matrix composite material, such as... Figure 1 As shown, it includes the following steps:
[0054] S1. Using soft domains as the first and last layers, nine layers of soft domain and hard domain material powder are stacked alternately, totaling five layers of soft domain powder and four layers of hard domain powder. Odd-numbered layers are soft domain powder and even-numbered layers are hard domain powder. A nine-layer composite material is prepared by spark plasma sintering.
[0055] S2. The composite material is subjected to multiple cold rolling passes with a reduction of 90%, and then annealed at 400°C for 10 minutes at a reduction of 50%.
[0056] S3. After multiple cold rolling passes, the rolled composite material is subjected to heat treatment, which includes solution heat treatment and aging heat treatment. The holding temperature of solution heat treatment is 550-570℃ and the holding time is 5-60 min. The holding temperature of aging heat treatment is 150-200℃ and the holding time is 1-5 h. After the heat treatment is completed, a dual heterogeneous particle reinforced aluminum matrix composite material is obtained.
[0057] Furthermore, through comparison and analysis, in step S3, the solution heat treatment had a holding temperature of 570℃ and a holding time of 30 min; in step S3, the aging heat treatment had a holding temperature of 175℃ and a holding time of 3 h. The composite material obtained through these ranges of solution heat treatment and aging heat treatment exhibited the best mechanical properties.
[0058] According to the above technical solution, the present invention comprises sintering fine-grained 6061 aluminum alloy powder, TiC nanoparticle reinforcement, and coarse-grained 6061 aluminum alloy powder in 9 layers to obtain an alloy ingot. In this embodiment, the fine-grained 6061 aluminum alloy powder is preferably powder with a particle size of <10μm, the TiC nanoparticle reinforcement is preferably powder with a particle size of 50nm, and the coarse-grained 6061 aluminum alloy powder is preferably powder with a particle size of 45-150μm.
[0059] In this embodiment, 99.5 vol.% fine-grained 6061 aluminum alloy powder and 0.5 vol.% TiC nanoparticle reinforcement are pretreated and mixed. Mixing is preferably carried out in a glove box, with argon as the protective gas during loading. In this invention, the grinding jar is preferably a tungsten carbide grinding jar; the preferred diameter ratio of the three steel balls is 8 mm, 6 mm, and 2 mm, and the preferred weight ratio is 2:3:5; the ball-to-material ratio is 8:1. In this invention, the ball milling in step S1 includes the following steps:
[0060] Fine-grained 6061 aluminum alloy powder and TiC nanoparticle reinforcement are mixed in a planetary ball mill at a rotation speed of 150-250 rpm, more preferably 200 rpm. In a specific embodiment of the present invention, the optimal operating time of the planetary ball mill is 2-2.5 hours, preferably 2 hours, with a 10-minute pause after every 15 minutes of operation.
[0061] In a specific embodiment of the present invention, sintering in step S1 includes the following steps:
[0062] The nine-layer composite material was sintered in a spark plasma system. The temperature and pressure increase process during sintering was as follows: 0-2 min, temperature increased to 20℃; 2-6 min, temperature increased to 100℃; 6-12 min, temperature increased to 200℃; 12-20 min, temperature increased to 300℃; 20-32 min, temperature increased to 400℃; 32-48 min, temperature increased to 530℃; 48-50 min, temperature increased to 540℃; 50-52 min, temperature increased to 550℃; 52-54 min, temperature increased to 560℃; 54-57 min, temperature was maintained at 560℃. The pressure was maintained at 50 MPa from 2 min to 57 min. Cooling was performed in-furnace cooling followed by pressure relief, yielding the composite material.
[0063] In a specific embodiment of the present invention, step S2 of multi-pass cold rolling includes the following steps:
[0064] The composite material is subjected to multi-pass cold rolling, preferably 7-12 passes, more preferably 9 passes. In a specific embodiment of the invention, when the rolling deformation is 50%, annealing at 400°C for 10 minutes is performed. Multi-pass rolling is preferably carried out in a two-roll flat mill, and the reduction in rolling depth for each pass is preferably 1.5-2 mm. The total deformation of the alloy ingot after multi-pass cold rolling is preferably 90%.
[0065] In a specific embodiment of the present invention, the heat treatment in step S3 includes the following steps: solution heat treatment and aging heat treatment; firstly, the composite material after multi-pass cold rolling is subjected to solution heat treatment, the holding temperature of solution heat treatment is preferably 570℃, and the holding time of solution heat treatment is preferably 5-60min, more preferably 30min; then, the composite material after solution heat treatment is subjected to aging heat treatment, the holding temperature of aging heat treatment is preferably 150-200℃, more preferably 175℃, and the holding time of aging heat treatment is preferably 1-5h, more preferably 3h.
[0066] The present invention enables the complete re-dissolution of the precipitated phase through solution heat treatment, causing lattice distortion, improving strength, and promoting the recrystallization process; the present invention enables the precipitation of a second phase through aging heat treatment, thereby strengthening the strength through precipitation.
[0067] After heat treatment, the obtained alloy sheet is post-treated to obtain a high-strength and high-plasticity dual heterogeneous particle-reinforced aluminum matrix composite material. In this invention, the cooling method for solution heat treatment is water cooling, and the cooling method for aging heat treatment is air cooling.
[0068] This invention provides the application of high-strength and high-plasticity dual heterogeneous particle-reinforced aluminum matrix composite materials, or high-strength and high-plasticity dual heterogeneous particle-reinforced aluminum matrix composite materials prepared by the above-mentioned technical solutions, in fields such as fighter jet ventral fins or automotive parts such as piston anti-wear rings, automotive connecting rods, brake discs, engine pistons, and gearboxes.
[0069] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0070] Example 1
[0071] Samples were loaded into an argon-filled glove box. 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size of 50 nm were placed in a tungsten carbide canister. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten carbide canister was filled with argon and sealed, then placed in a planetary ball mill at 200 rpm. The mill operated for 15 minutes followed by a 10-minute pause, for a total of 2 hours. The resulting mixed powder was designated as the hard domain. Coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < 150 μm was designated as the soft domain.
[0072] Starting with the soft domain, nine layers of soft and hard domains were stacked alternately, compacted, and then placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm was obtained and cooled in the furnace to obtain the sintered particle-reinforced aluminum matrix composite material of this invention. The heating and pressurization process was as follows: 0 min - 2 min, temperature increased to 20°C; 2 min - 6 min, temperature increased to 100°C; 6 min - 12 min, temperature increased to 200°C; 12 min - 20 min, temperature increased to 300°C; 20 min - 32 min, temperature increased to 400°C; 32 min - 48 min, temperature increased to 530°C; 48 min - 50 min, temperature increased to 540°C; 50 min - 52 min, temperature increased to 550°C; 52 min - 54 min, temperature increased to 560°C; 54 min - 57 min, temperature maintained at 560°C. The pressure was maintained at 50 MPa from 2 min - 57 min.
[0073] Figure 2 The image shows the OM diagram of the sintered dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 1 of the present invention. The average grain size of the coarse-grained region is 53 μm, the average grain size of the fine-grained region is 417 nm, and the boundary bonding is tight.
[0074] Example 2
[0075] Samples were loaded into an argon-filled glove box. 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size of 50 nm were placed in a tungsten carbide jar. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten carbide jar was filled with argon and sealed, then placed in a planetary ball mill at 200 rpm. The mill operated for 15 minutes followed by a 10-minute pause, for a total of 2 hours. The resulting mixed powder was designated as the hard domain. Coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < 150 μm was designated as the soft domain.
[0076] Starting with the soft domain, the soft and hard domains are stacked in an alternating order to form nine layers. After compaction, they are placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm is obtained and then cooled in the furnace.
[0077] The cylindrical sample was subjected to multiple cold rolling passes, with each pass reducing the sample by 10% and the total reduction being 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.
[0078] Figure 3 The image shows the OM diagram of the cold-rolled dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 2 of the present invention. The gray area represents the coarse-grained region, and the brown area represents the fine-grained region. The grains in the coarse-grained region are elongated along the rolling direction, while the grains in the fine-grained region still maintain the nanoscale size.
[0079] Example 3
[0080] Samples were loaded into an argon-filled glove box. 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size of 50 nm were placed in a tungsten carbide jar. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten carbide jar was filled with argon and sealed, then placed in a planetary ball mill at 200 rpm. The mill operated for 15 minutes followed by a 10-minute pause, for a total of 2 hours. The resulting mixed powder was designated as the hard domain. Coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < 150 μm was designated as the soft domain.
[0081] Starting with the soft domain, nine layers of soft and hard domains were stacked alternately, compacted, and then placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm was obtained and cooled in the furnace. The heating and pressurization process was as follows: 0 min - 2 min, temperature increased to 20℃; 2 min - 6 min, temperature increased to 100℃; 6 min - 12 min, temperature increased to 200℃; 12 min - 20 min, temperature increased to 300℃; 20 min - 32 min, temperature increased to 400℃; 32 min - 48 min, temperature increased to 530℃; 48 min - 50 min, temperature increased to 540℃; 50 min - 52 min, temperature increased to 550℃; 52 min - 54 min, temperature increased to 560℃; 54 min - 57 min, temperature maintained at 560℃. The pressure was maintained at 50 MPa from 2 min - 57 min.
[0082] The cylindrical sample was subjected to multiple cold rolling passes, with each pass reducing the sample by 10% and the total reduction being 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.
[0083] The cold-rolled sheet is placed in a muffle furnace and dissolved at 570°C for 5 minutes, followed by water cooling.
[0084] Figure 4 The image shows the OM diagram of the double heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 3 of this invention after solution heat treatment at 570℃ for 5 min. The gray area represents the coarse-grained region, and the brown area represents the fine-grained region. The grains in the coarse-grained region are elongated along the rolling direction, while the grains in the fine-grained region still maintain the nanoscale size.
[0085] Example 4
[0086] Samples were loaded into an argon-filled glove box. 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size of 50 nm were placed in a tungsten carbide canister. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten carbide canister was filled with argon and sealed, then placed in a planetary ball mill at 200 rpm. The mill operated for 15 minutes followed by a 10-minute pause, for a total of 2 hours. The resulting mixed powder was designated as the hard domain. Coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < 150 μm was designated as the soft domain.
[0087] Starting with the soft domain, nine layers of soft and hard domains were stacked alternately, compacted, and then placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm was obtained and cooled in the furnace. The heating and pressurization process was as follows: 0 min - 2 min, temperature increased to 20℃; 2 min - 6 min, temperature increased to 100℃; 6 min - 12 min, temperature increased to 200℃; 12 min - 20 min, temperature increased to 300℃; 20 min - 32 min, temperature increased to 400℃; 32 min - 48 min, temperature increased to 530℃; 48 min - 50 min, temperature increased to 540℃; 50 min - 52 min, temperature increased to 550℃; 52 min - 54 min, temperature increased to 560℃; 54 min - 57 min, temperature maintained at 560℃. The pressure was maintained at 50 MPa from 2 min - 57 min.
[0088] The cylindrical sample was subjected to multiple cold rolling passes, with each pass reducing the sample by 10% and the total reduction being 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.
[0089] The cold-rolled sheet is placed in a muffle furnace and solution-treated at 570°C for 30 minutes, followed by water cooling.
[0090] Figure 5 The image shows the OM diagram of the double heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 4 of this invention after solution heat treatment at 570℃ for 30 min. In the image, the gray area represents the coarse-grained region and the brown area represents the fine-grained region. The grains in the coarse-grained region are elongated along the rolling direction, while the grains in the fine-grained region still maintain the nanoscale size.
[0091] Example 5
[0092] Samples were loaded into an argon-filled glove box. 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size of 50 nm were placed in a tungsten carbide canister. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten carbide canister was filled with argon and sealed, then placed in a planetary ball mill at 200 rpm. The mill operated for 15 minutes followed by a 10-minute pause, for a total of 2 hours. The resulting mixed powder was designated as the hard domain. Coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < 150 μm was designated as the soft domain.
[0093] Starting with the soft domain, the soft and hard domains are stacked in an alternating order to form nine layers. After compaction, they are placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm is obtained and then cooled in the furnace.
[0094] The heating and pressurization process is as follows: 0 min - 2 min, temperature rises to 20℃; 2 min - 6 min, temperature rises to 100℃; 6 min - 12 min, temperature rises to 200℃; 12 min - 20 min, temperature rises to 300℃; 20 min - 32 min, temperature rises to 400℃; 32 min - 48 min, temperature rises to 530℃; 48 min - 50 min, temperature rises to 540℃; 50 min - 52 min, temperature rises to 550℃; 52 min - 54 min, temperature rises to 560℃; 54 min - 57 min, temperature is maintained at 560℃. 2 min - 57 min, pressure is maintained at 50 MPa.
[0095] The cylindrical sample was subjected to multiple cold rolling passes, with each pass reducing the sample by 10% and the total reduction being 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.
[0096] The cold-rolled sheet is placed in a muffle furnace and solution-treated at 570°C for 60 minutes, followed by water cooling.
[0097] Figure 6 The image shows the OM diagram of the double heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 5 of the present invention after solution heat treatment at 570℃ for 60 min. In the image, the gray area represents the coarse-grained region and the brown area represents the fine-grained region. The grains in the coarse-grained region are elongated along the rolling direction, while some grains in the fine-grained region undergo secondary recrystallization.
[0098] Example 6
[0099] Samples were loaded into an argon-filled glove box. 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size of 50 nm were placed in a tungsten carbide canister. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten carbide canister was filled with argon and sealed, then placed in a planetary ball mill at 200 rpm. The mill operated for 15 minutes followed by a 10-minute pause, for a total of 2 hours. The resulting mixed powder was designated as the hard domain. Coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < 150 μm was designated as the soft domain.
[0100] Starting with the soft domain, nine layers of soft and hard domains were stacked alternately, compacted, and then placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm was obtained and cooled in the furnace. The heating and pressurization process was as follows: 0 min - 2 min, temperature increased to 20℃; 2 min - 6 min, temperature increased to 100℃; 6 min - 12 min, temperature increased to 200℃; 12 min - 20 min, temperature increased to 300℃; 20 min - 32 min, temperature increased to 400℃; 32 min - 48 min, temperature increased to 530℃; 48 min - 50 min, temperature increased to 540℃; 50 min - 52 min, temperature increased to 550℃; 52 min - 54 min, temperature increased to 560℃; 54 min - 57 min, temperature maintained at 560℃. The pressure was maintained at 50 MPa from 2 min - 57 min.
[0101] The cylindrical sample was subjected to multiple cold rolling passes, with each pass reducing the sample by 10% and the total reduction being 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.
[0102] The cold-rolled sheet is placed in a muffle furnace and solution-treated at 570°C for 30 minutes, followed by water cooling.
[0103] The plate that has undergone solution heat treatment is placed in a muffle furnace and subjected to aging heat treatment at 175°C for 1 hour, followed by air cooling, to obtain the high-strength and high-plasticity dual heterogeneous particle-reinforced aluminum matrix composite material of the present invention.
[0104] Figure 7 The image shows a TEM image of the aluminum matrix composite material with dual heterogeneous particles after aging heat treatment at 175℃ for 1 hour prepared in Example 6 of this invention. The matrix contains a large number of coherent GP regions and a small amount of coherent β” phase, which is a typical under-failure state.
[0105] Example 7
[0106] Samples were loaded into an argon-filled glove box. 99.5 vol.% of fine-grained 6061 aluminum alloy with a particle size <10 μm and 0.5 vol.% of TiC nanoparticle reinforcement with a particle size of 50 nm were placed in a tungsten carbide canister. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. The tungsten carbide canister was filled with argon and sealed, then placed in a planetary ball mill at 200 rpm. The mill operated for 15 minutes followed by a 10-minute pause, for a total of 2 hours. The resulting mixed powder was designated as the hard domain. Coarse-grained 6061 aluminum alloy powder with a particle size of 45 μm < 150 μm was designated as the soft domain.
[0107] Starting with the soft domain, the soft and hard domains are stacked in an alternating order to form nine layers. After compaction, they are placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45 mm and a height of 18 mm is obtained and then cooled in the furnace.
[0108] The cylindrical sample was subjected to multiple cold rolling passes, with each pass reducing the sample by 10% and the total reduction being 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.
[0109] The cold-rolled sheet is placed in a muffle furnace and solution-treated at 570°C for 30 minutes, followed by water cooling.
[0110] The plate that has undergone solution heat treatment is placed in a muffle furnace and subjected to aging heat treatment at 175°C for 3 hours, followed by air cooling, to obtain the high-strength and high-plasticity dual heterogeneous particle-reinforced aluminum matrix composite material of the present invention.
[0111] Figure 8 The image shows a TEM image of the aluminum matrix composite material reinforced with two heterogeneous particles after aging heat treatment at 175℃ prepared in Example 7 of this invention. The matrix contains a large number of coherent β” phases, which are in the peak aging state and can ensure the high strength of the material.
[0112] Example 8
[0113] The sample was loaded into an argon-filled glove box. 99.5 vol.% fine-grained 6061 aluminum alloy (particle size <10 μm) and 0.5 vol.% TiC nanoparticle reinforcement (particle size = 50 nm) were placed into a tungsten carbide jar. The steel balls had diameters of 8 mm, 6 mm, and 2 mm, with a weight ratio of 2:3:5 and a ball-to-material ratio of 8:1. After filling the tungsten carbide jar with argon gas and sealing it, the jar was placed in a planetary ball mill. The planetary ball mill rotated at 200 rpm, operating for 15 minutes followed by a 10-minute pause, for a total operation time of 2 hours.
[0114] The powder was stacked into nine layers in an alternating order of coarse-grained 6061 aluminum alloy powder (45μm < particle size < 150μm) and fine-grained 6061 aluminum alloy powder (particle size < 10μm) + TiC nanoparticle reinforcement (particle size = 50nm). After compaction, it was placed in a spark plasma sintering system. After heating and pressurization, a cylindrical sample with a diameter of 45mm and a height of 18mm was obtained and cooled with the furnace.
[0115] The cylindrical sample was subjected to multiple cold rolling passes, with each pass reducing the sample by 10% and the total reduction being 90%. When the reduction was 50%, the sample was placed in a muffle furnace and annealed at 400°C for 10 minutes.
[0116] The cold-rolled sheet is placed in a muffle furnace and dissolved at 570°C for 5 minutes, followed by water cooling.
[0117] The plate that has undergone solution heat treatment is placed in a muffle furnace and subjected to aging heat treatment at 175°C for 5 hours, followed by air cooling, to obtain the high-strength and high-plasticity dual heterogeneous particle-reinforced aluminum matrix composite material of the present invention.
[0118] Figure 9 The image shows a TEM image of the aluminum matrix composite material reinforced with two heterogeneous particles after aging heat treatment at 175℃ for 5 hours prepared in Example 8 of this invention. A large number of semi-coherent β' phases are distributed in the matrix, indicating an over-aged state.
[0119] Test Example 1
[0120] The yield strength, ultimate tensile strength and elongation of the products in Examples 2-8 were tested according to GB / T228-1987 "Metallic Materials - Tensile Testing". The results are listed in Table 1. From the data in Table 1, it can be seen that the yield strength of the dual heterogeneous particle-reinforced aluminum matrix composite material prepared in Example 7 of this invention is 379.4 MPa, the tensile strength is 405.7 MPa and the total elongation is 12.7%, which realizes the high strength and high plasticity of the particle-reinforced aluminum matrix composite material.
[0121] Table 1 shows the test results of the mechanical properties of the alloys prepared in Examples 2-8.
[0122]
[0123] As can be seen from the table above, the aluminum matrix composite material reinforced with dual heterogeneous particles proposed in this invention exhibits excellent mechanical properties with synergistic improvement in strength and plasticity. The results of the embodiments of this invention show that the yield strength of the aluminum matrix composite material reinforced with dual heterogeneous particles provided by this invention is 379.4 MPa, the ultimate tensile strength is 405.7 MPa, and the elongation is 12.7%. Its comprehensive mechanical properties are significantly improved compared to existing methods.
[0124] The embodiments described above are merely preferred embodiments of the present invention and are not intended to limit the scope of the present invention. Various modifications and improvements made by those skilled in the art to the technical solutions of the present invention without departing from the spirit of the present invention should fall within the protection scope defined by the claims of the present invention.
Claims
1. A dual heterogeneous particle-reinforced aluminum matrix composite material, characterized in that: It consists of nine layers of alternating stacked and cold-rolled soft and hard regions. The soft regions are coarse-grained 6061 aluminum alloy homogeneous materials, and the hard regions are composite materials composed of fine-grained 6061 aluminum alloy and TiC nanoparticle reinforcement. The preparation method of the dual heterogeneous particle-reinforced aluminum matrix composite material includes the following steps: S1. Using a soft domain as the first layer, nine layers of hard and soft domain material powders are alternately stacked and compacted, and then a nine-layer composite material is prepared by spark plasma sintering. S2. The composite material is subjected to multiple cold rolling passes with a total reduction of 90%, and then annealed at 400°C for 10 minutes at 50% reduction. S3. After multiple cold rolling passes, the rolled composite material is subjected to heat treatment, which includes solution heat treatment and aging heat treatment. The holding temperature of the solution heat treatment is 550-570℃ and the holding time of the solution heat treatment is 5-60 min. The holding temperature of the aging heat treatment is 150-200℃ and the holding time of the aging heat treatment is 1-5 h. After the heat treatment is completed, a dual heterogeneous particle reinforced aluminum matrix composite material is obtained.
2. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: The volume ratio of 6061 aluminum alloy to TiC nanoparticle reinforcement in the hard domain is 99.5:0.
5.
3. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: In step S3, the solution heat treatment is performed at a holding temperature of 570°C for 30 minutes. In step S3, the aging heat treatment is performed at a holding temperature of 175°C for 3 hours.
4. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: Cold-rolled composite materials include three deformation stages. The first deformation stage is an elastic deformation process, which is the same as that of homogeneous materials. The second deformation stage is an elastoplastic transition process. Stress activates dislocation sources in the soft domain, causing plastic deformation, while the hard domain maintains elastic strain, resulting in mechanical incompatibility. The hard domain constraint restricts and increases the strain in the soft domain, and a strain gradient is generated at the domain interface. The properties of the soft and hard domains are changed through geometrically necessary dislocation coordination, which improves the overall yield strength. Dislocation pile-up occurs at the soft domain interface, and dislocation sources require additional stress to excite dislocations. The heterogeneous deformation induced stress is generated through geometrically necessary dislocation pile-up, which strengthens the soft domain. The third deformation stage is the surface strain distribution process. Continuous strain causes the hard domain to begin plastic deformation, strain distribution increases the strain in the soft domain, and the strain gradient at the boundary between the soft and hard domains increases. Through the accumulation of a large number of geometrically necessary dislocations, strain hardening ability is provided to prevent necking, so that the composite material has both high strength and high plasticity.
5. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: Step S1 specifically includes the following sub-steps: S11. Preparation of hard domain powder: 99.5 vol.% of 6061 aluminum alloy powder and 0.5 vol.% TiC nanoparticle reinforcement were placed in a planetary ball mill for ball milling and mixing. The planetary ball mill contained three types of steel balls with diameters of 8 mm, 6 mm and 2 mm, respectively, in a mass ratio of 2:3:5 and a ball-to-material ratio of 8:1, to obtain hard domain powder after ball milling. S12. Coarse-grained 6061 aluminum alloy powder and ball-milled hardened powder are alternately stacked into 9 layers, compacted, and then placed in a spark plasma sintering system to apply temperature and pressure to prepare a sintered 9-layer composite material.
6. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: The obtained dual heterogeneous particle-reinforced aluminum matrix composite has a yield strength of 379.4 MPa, an ultimate tensile strength of 405.7 MPa, and an elongation of 12.7%.
7. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: The fine-grained 6061 aluminum alloy powder has a particle size of <10 micrometers, the TiC nanoparticle reinforcement has a particle size of 50 nanometers, and the coarse-grained 6061 aluminum alloy powder has a particle size of greater than 45 micrometers and less than 150 micrometers.
8. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: In step S11, argon is used as a protective atmosphere during the powder loading process; the total working time of the planetary ball mill is 2-2.5 hours, with a 10-minute stop after 15 minutes of operation, and a rotation speed of 150-200 rpm.
9. The aluminum matrix composite material reinforced with dual heterogeneous particles according to claim 1, characterized in that: In step S12, the sintering heating and pressurization process is as follows: 0 min - 2 min, temperature rises to 20℃; 2 min - 6 min, temperature rises to 100℃; 6 min - 12 min, temperature rises to 200℃; 12 min - 20 min, temperature rises to 300℃; 20 min - 32 min, temperature rises to 400℃; 32 min - 48 min, temperature rises to 530℃; 48 min - 50 min, temperature rises to 540℃; 50 min - 52 min, temperature rises to 550℃; 52 min - 54 min, temperature rises to 560℃; 54 min - 57 min, temperature is maintained at 560℃; 2 min - 57 min, pressure is maintained at 50 MPa.
Citation Information
Patent Citations
Aluminum alloy profile with mixed crystal heterostructure characteristic and preparation method
CN116479281A
Method of producing uniform blends of NANO and micron powders
WO2008034043A2